Analisis Pengaruh NPF, FDR, CAR, dan GCG terhadap Profitabilitas Bank Umum Syariah - Sarah Salsabila; Ruhadi Ruhadi; Banter Laksana; Nafisah Ruhana (Journal of Applied Islamic Economics and Finance, 2023)
This study aims to examine the effect of NPF, FDR, CAR and GCG on the profitability of Islamic commercial banks. The data used is secondary data in the form of annual financial reports from 10 Islamic Commercial Banks in Indonesia registered with the Financial Services Authority for the 2017-2020 period. The independent variables used are NPF, FDR, CAR, and GCG which are proxied by the board of directors, independent board of commissioners, and sharia supervisory board. While the dependent variable used is return on assets (ROA). Testing this hypothesis uses a path diagram that is processed with WarpPLS version 8.0. The results of this study indicate that the NPF, FDR, CAR and the sharia supervisory board have significant effect on the profitability of Islamic commercial banks, while the independent board of directors and commissioners have no significant effect on the profitability of Islamic commercial banks.